2021
DOI: 10.17582/journal.jahp/2021/9.s1.34.41
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping, Antibiotic Resistance and Biofilm Formation Ability of Clostridium perfringens Isolated from Raw Milk, Dairy Products and Human Consumers

Eman Y.T. Elariny,
Heba A. Ahmed,
Amany A.H. Khatab
et al.

Abstract: Clostridium perfringens is one of the most common causes of food poisoning in the world. In this study, C. perfringens isolated from raw milk, milk products and human consumers were investigated for their antibiotic resistance and biofilm formation ability. A total of 460 samples (buffalo milk, cow milk, camel milk, yoghurt, Kareish cheese and soft (processed) cheese, 60 of each and 100 diarrheic stool sample of human consumers) were collected from Zagazig city, Sharkia Governorate, Egypt, and examined for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
(42 reference statements)
1
0
0
Order By: Relevance
“…This might be due to the frequent use of this antibiotic in poultry production to get utmost production (Mohsin et al, 2019). Our results are also in agreement with the study of Elariny et al, (2021), who reported the resistant behavior of C. perfringens against oxytetracycline (87.5%), amoxicillin (83.4%), ampicillin and erythromycin (75%).…”
Section: Antibiogram Of C Perfringens Isolatessupporting
confidence: 92%
“…This might be due to the frequent use of this antibiotic in poultry production to get utmost production (Mohsin et al, 2019). Our results are also in agreement with the study of Elariny et al, (2021), who reported the resistant behavior of C. perfringens against oxytetracycline (87.5%), amoxicillin (83.4%), ampicillin and erythromycin (75%).…”
Section: Antibiogram Of C Perfringens Isolatessupporting
confidence: 92%